From Celebrity to Micro-Influencers: Strategic Trade-Offs in Brand Selection of Influencer Marketing Approaches - Julius Sutrisno; Antonius Felix; Reynard J.N. Makarawung; Derick Raditya (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
Influencer marketing is strategically important in digital markets, yet prior research largely focuses on consumer responses, neglecting brand-level decisions on influencer types. In Islamic business and ethical marketing, credibility and authenticity are crucial as Muslim consumers value trustworthiness and honest communication. This study analyzes brand considerations when choosing between celebrity endorsers and micro-influencers, focusing on trade-offs among reach, engagement, authenticity, and cost efficiency. A systematic literature review of peer-reviewed articles (2020–2025) from Scopus, Web of Science, and Google Scholar was conducted using thematic analysis. Findings reveal that influencer selection is shaped by internal factors (marketing objectives, budget, product characteristics, target market) and external factors (platform dynamics, competition, consumer behavior changes, reputational risks). Celebrity endorsers excel at enhancing brand awareness and symbolic value, while micro-influencers generate higher engagement, authenticity, and cost efficiency. The study concludes that influencer marketing should be treated as a strategic brand decision, not merely a promotional tactic. From an Islamic business ethics perspective, choosing micro-influencers reflects trustworthy, authentic, and ethically responsible communication, not just cost savings. Organizations must align influencer strategies with long-term brand communication goals for sustainable marketing effectiveness.